Pengaruh Penerapan Gaya Mengajar Komando Terhadap Gerak Dasar Servis Panjang Dalam Permainan Bulutangkis Pada Siswa SMP Negeri 3 Tondano - Natasya Momintan; Drs. Dj. A. Sungkudon M.Kes AIFO; Dr. Jan Lengkong M.Kes AIFO (STIKES Columbia Asia Medan, 2025)
This research aims to examine the influence of the command teaching style on students' long service skills in badminton games at SMP Negeri 3 Tondano. The study employed an experimental design with a randomized control group using pre-test and post-test assessments. The participants consisted of 22 students divided into experimental and control groups, each comprising 11 students. Data were gathered using a long service skill test. The results of the t-test analysis showed a significant difference, with tcount = 8.28 exceeding ttable = 2.086. These findings indicate that the command teaching style effectively enhances students' long service abilities in badminton.